2019
DOI: 10.1111/jace.16964
|View full text |Cite
|
Sign up to set email alerts
|

Carbon vacancy ordering in zirconium carbide powder

Abstract: Ordered carbon vacancies were detected in zirconium carbide (ZrCx) powders that were synthesized by direct reaction. Zirconium hydride (ZrH2) and carbon black were used as starting powders with the molar ratio of ZrH2:C = 1:0.6. Powders were reacted at 1300°C or 2000°C. The major phase detected by x‐ray diffraction (XRD) was ZrCx. No excess carbon was observed by transmission electron microscopy (TEM) in powders synthesized at either temperature. Ordering of the carbon vacancies was identified by neutron powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
6
11
0
Order By: Relevance
“…Additionally, Zr 2 C can tolerate more oxygen than other ordered phases due to its larger ordering energy at a given oxygen concentration. This is consistent with the Zr 2 C phase being the most-oen experimentally synthesised ordered zirconium carbide, being reported twice as oen 4,6,8,9,[11][12][13] as all other ordered structures combined. 4,7,8,10…”
Section: Destabilisation Of the Ordered Phasessupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, Zr 2 C can tolerate more oxygen than other ordered phases due to its larger ordering energy at a given oxygen concentration. This is consistent with the Zr 2 C phase being the most-oen experimentally synthesised ordered zirconium carbide, being reported twice as oen 4,6,8,9,[11][12][13] as all other ordered structures combined. 4,7,8,10…”
Section: Destabilisation Of the Ordered Phasessupporting
confidence: 87%
“… 3 Various vacancy-ordered phases have been intermittently reported in the experimental literature but there is no consensus regarding phase stability. Goretzki observed a Zr 2 C superlattice, 6 Obata and Nakazawa unsuccessfully attempted to fabricate Zr 2 C, but observed Zr 4 C 3 , 7 de Novion and Maurice reported the Zr 2 C phase, 8 Karimov et al reported Zr 2 C, 9 Khaenko et al reported possible trigonal Zr 8 C 5 , 10 Hu et al observed Zr 2 C superstructures, 11 Wei et al reported Zr 2 C, 12 Zhou et al fabricated Zr 2 C, 13 and Rana et al reported possible systematic vacancy ordering. 4 Theoretical calculations confirm that long-range superstructural ordering of vacancies is expected at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The orderdisorder phase boundaries calculated by Gusev and Rempel separate the regions where some degree of long-range ordering occurs and where a fully disordered solid solution is expected. The second-order reaction, Zr 2 C→ ZrC x , has a maximum transformation temperature of 1219 K (946 phase is consistent in structure with the cubic and trigonal experimental observations, 21,[25][26][27]31,34 and the orderdisorder transition temperatures are consistent with the transition at ∼1170 K (∼897 • C) for ZrC 0.63 measured by Karimov et al 26 The disordering temperature is also consistent with measurements by Obata and Nakazawa of 1340 K (1067 • C) for ZrC 0.70 , 22 although the Zr 4 C 3 structure determined in that work is not found in the calculated phase diagram. Despite Zr 3 C 2 and Zr 6 C 5 not having been observed experimentally, Gusev et al believed them to be stable on the basis of comparison with the observed analogous Ti 3 C 2 phase and investigations of this composition range.…”
Section: Gusev Andsupporting
confidence: 62%
“…In principle, if the carbon loss during carbonization (degradation into volatile organic materials or CO/CO 2 ) is less than 58 mass % for 2-DVB-Zr samples or 66% for 8-DVB-Zr samples, then the residual carbon content in the solid phase is larger than is required to form stoichiometric ZrC. Depending on the amount of volatile carbon compounds (it depends on pressure, temperature, time and heating method) and the carbon loss during pyrolysis, the residual Zr/C ratio in nano-ZrO 2 @C and nano-ZrC@C composites can be increased and only ZrC products with a carbon vacancy (ZrC 0.63−0.98 [23]) may be created.…”
Section: Preparation and Properties Of Zr-loaded Ion-exchangers (2-dv...mentioning
confidence: 99%
“…Zirconium carbide ceramic materials formed in direct reactions of Zr or Zr compounds and carbon or carbon precursors, even in the case of the most reactive ZrH 2 , always contains some carbon vacancy [16]. The reaction of carbondeficient ZrC x structures with the free carbon results in the formation of non-stoichiometric Zr 1-x C (carbon-rich) materials and increases their sinterability [23].…”
Section: Introductionmentioning
confidence: 99%